2021
DOI: 10.1001/jamanetworkopen.2021.25544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hearing Screening Combined With Limited and Expanded Genetic Screening for Newborns in Nantong, China

Abstract: Key Points Question Is the modified newborn genetic and hearing screening feasible in China? Findings In this population-based cohort study including 32 512 infants, incorporating the limited and expanded genetic screening into physiological screening was associated with identifying 31 newborns with hearing loss missed by the conventional hearing screening, providing etiologic information to 1299 participants, and targeting 517 children at risk of late-onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Patients with variants in SLC26A4 , which may lead to sudden hearing loss after head trauma or barotrauma, were strongly advised to avoid situations that may result in sudden changes in intracranial pressure, to prevent or delay the occurrence of hearing loss. 55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with variants in SLC26A4 , which may lead to sudden hearing loss after head trauma or barotrauma, were strongly advised to avoid situations that may result in sudden changes in intracranial pressure, to prevent or delay the occurrence of hearing loss. 55 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with variants in SLC26A4, which may lead to sudden hearing loss after head trauma or barotrauma, were strongly advised to avoid situations that may result in sudden changes in intracranial pressure, to prevent or delay the occurrence of hearing loss. 55 Expanded genomic sequencing combined with NBHS is useful for diagnosing hearing loss, managing patients, monitoring progression, genetic counseling, and educating patients on the prevention of precipitating factors. It also highlights the importance of follow-up for preventing or delaying the occurrence of hearing loss and of early diagnosis for prompt treatment of late-onset hearing loss if it occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 2019; Guo et al 2020). Many studies have demonstrated the benefits of incorporating genetic screening into universal newborn hearing screening programs, especially for common deafness-associated variants (Kenna 2021; Zhu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This will certainly result in early audiologic and etiologic detection of HL with its many benefits to be realized. [155][156][157]…”
Section: Future Perspectivesmentioning
confidence: 99%